The role of the general and provincial chapters in improving and enforcing accounting, financial and management controls in Benedictine monasteries in England 1215–1444. Issue 2 (June 2015) - Dobie, Alisdair
Abstract: Allegations of mismanagement have played a major part in the sometimes acrimonious debate between historians on the state of monasticism in later medieval England. Contemporaries were aware of such problems and Benedictine Chapters (assemblies of the heads of monastic houses with the power to make statutes binding on all houses) issued a large amount of regulation to address these issues. This paper analyses the statutes issued by the Chapters to identify those concerned with the financial management of monasteries. The analysis reveals a concern with transparency in financial transactions, evident in efforts to extend knowledge of the financial transactions of a house beyond the immediate participants to the wider monastic community, even requiring its consent for transactions to be considered valid. Additionally, it finds an increasing level of definition both in terms of the preparation and audit of accounts and in the wider control environment. The process of visitation, by which the temporal and spiritual health of monastic houses was monitored, and their adherence to Chapter statutes confirmed, may be regarded as an early attempt at quality control aimed at the maintenance of high standards in religious life. The Chapters can be seen to be an important instrument for the dissemination of improved accounting practices, and the emphasis upon the management of temporalities within Chapter statutes allows further insights into the alleged sacred-secular dichotomy. Accounting and accountability are found to be an essential component in the life of a healthy Benedictine monastery.